7(k-2)=7(6k-7)

Simple and best practice solution for 7(k-2)=7(6k-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(k-2)=7(6k-7) equation:


Simplifying
7(k + -2) = 7(6k + -7)

Reorder the terms:
7(-2 + k) = 7(6k + -7)
(-2 * 7 + k * 7) = 7(6k + -7)
(-14 + 7k) = 7(6k + -7)

Reorder the terms:
-14 + 7k = 7(-7 + 6k)
-14 + 7k = (-7 * 7 + 6k * 7)
-14 + 7k = (-49 + 42k)

Solving
-14 + 7k = -49 + 42k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-42k' to each side of the equation.
-14 + 7k + -42k = -49 + 42k + -42k

Combine like terms: 7k + -42k = -35k
-14 + -35k = -49 + 42k + -42k

Combine like terms: 42k + -42k = 0
-14 + -35k = -49 + 0
-14 + -35k = -49

Add '14' to each side of the equation.
-14 + 14 + -35k = -49 + 14

Combine like terms: -14 + 14 = 0
0 + -35k = -49 + 14
-35k = -49 + 14

Combine like terms: -49 + 14 = -35
-35k = -35

Divide each side by '-35'.
k = 1

Simplifying
k = 1

See similar equations:

| t^2-10+25=0 | | x-(4/x) | | -4(t-5)+8t=7t-4 | | 5t^2-15t+10=5t^2-2t | | y/96=3 | | (6xy-y^2)dx+(4y+3x^2)dy=0 | | 2(83-8)=8+72(89+8) | | y/42=3 | | 20=8+y | | 3(y-5)/5=-3y | | 5t^2-15+10=5t^2-2t | | -6+2r=-18 | | 1.46x=7.30 | | 41y=164 | | 10x-6=6x+12 | | 5(7x+1)-1=35x+4 | | 7y=-6x-15 | | k-(3/10)=(2/5) | | y/19=21 | | q+8=25 | | x+1.09=4 | | P-11=28 | | 55=.5(285-10e) | | h-6=9 | | Ln(4t-5)=2 | | 7+z=7 | | 5n+yr=r-7g | | x+1=117 | | 5.25x=68.25 | | x=117 | | .14(y-3)+.08y=0.16y-0.03(30) | | 2y-1=y+6 |

Equations solver categories